The Effect of ROA, EPS, and DER on Share Prices Of Insurance Companies Listed on the IDX (2020-2024) - Marni; Lestari, Dheri Febiyani (AKSIOMA : Jurnal Manajemen, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Earnings per Share (EPS), and Debt to Equity Ratio (DER) on stock prices in insurance companies listed on the Indonesia Stock Exchange for the period 2020-2024. The research method used is a quantitative approach with a causal associative research type. The data used are secondary data from insurance companies’ financial reports obtained through the Indonesia Stock Exchange. The research sample consisted of 9 insurance companies with a purposive sampling technique, resulting in 45 observational data points. The data analysis technique uses multiple linear regression with SPSS Statistics 26 through the classical assumption test, t-test, f-test, and coefficient of determination. The results show that ROA has a negative and significant effect on stock prices, while EPS and DER have a positive and significant effect on stock prices. Simultaneously, ROA, EPS, and DER have a significant effect on insurance companies’ stock prices.